Asbestos textile production linked to malignant peritoneal and pleural mesothelioma in women: Analysis of 28 cases in Southeast China. Issue 10 (6th July 2015) - Gao, Zhibin; Hiroshima, Kenzo; Wu, Xiaodong; Zhang, Jixian; Shao, Dichu; Shao, Huajiang; Yang, Hanqing; Yusa, Toshikazu; Kiyokawa, Takako; Kobayashi, Makio; Shinohara, Yasushi; Røe, Oluf D.; et al.
Abstract : Background: Chrysotile had been used in asbestos textile workshops in Southeast China but a clear relation to mesothelioma is lacking. Methods: All patients diagnosed with mesothelioma from 2003 to 2010 at Yuyao People's Hospital were re‐evaluated by multiple expert pathologists with immunohistochemistry and asbestos exposure data were collected. Results: Of 43 patients with a mesothelioma diagnosis, 19 peritoneal and nine pleural cases were finally diagnosed as mesothelioma. All were females, and the mean age of the patients with peritoneal or pleural mesothelioma was 52.4 and 58.2 years, respectively. All these cases had a history of domestic or occupational exposure to chrysotile. Two‐thirds of the patients were from two adjoining towns with multiple small asbestos textile workshops. Contamination of tremolite was estimated to be less than 0.3%. Conclusions: This is a report of mesothelioma in women exposed to chrysotile asbestos at home and at work, with an over‐representation of peritoneal mesothelioma. Am. J. Ind. Med. 58:1040–1049, 2015. © 2015 Wiley Periodicals, Inc.